Association between adverse childhood experiences and masculinity with well-being: moderating role of behavioural emotional regulation among men of three nations - P. Padma Sri Lekha; E. P. Abdul Azeez; Bhoomika N. Jadhav; Wafa Said Al-Maamari; Emad Farouk Saleh; A. P. Senthil Kumar (Scientific Reports)
Abstract The psychosocial aspects of men’s health and well-being have gained attention in the literature in recent years. However, evidence from developing countries is limited. Therefore, the present study attempted to understand the determining role of Adverse Childhood Experiences (ACEs) and masculinity on well-being factors, namely self-care and self-compassion among men, along with the moderating role of behavioral emotional regulation (BER) between masculinity and self-care. We adopted a cross-sectional study design. The data were collected from three countries, which are patriarchal societies, namely Ethiopia, India, and Oman, with a total sample size of 823 men between 18 and 45 years. Self-reported measures of the key variables were administered among the participants. We performed descriptive statistical analyses and path analysis. The ACEs were positively associated with masculinity (b = 1.544; 99% CI = 1.227–1.853), while it reduced the likelihood of self-compassion. Further, the increase in masculinity increased self-care (b = 0.195; 99% CI = 0.097- 0.295). However, the use of negative BER strategies reduced the likelihood of involvement in self-care (b=-1.185; 95% CI= -2.280- − 0.125) and changed the direction between masculinity and self-care (b=-0.644; 95% CI = − 0.988- − 0.279) acting as a moderator (b = 0.027; 95% CI = 0.003–0.051). The results suggest the importance of BER in effectively promoting self-care among men. Future self-care programs and interventions in the three nations should consider training men in BER. BER-focused interventions can facilitate positive coping among men and further enhance self-care and self-compassion.